Expanding the applicability of magnetic ionic liquids for multiclass determination in biological matrices based on dispersive liquid–liquid microextraction and HPLC with diode array detector analysis - Will, Camila; Omena, Eduarda; Corazza, Gabriela; Bernardi, Gabrieli; Merib, Josias; Carasek, Eduardo (Journal of separation science, 2020)
Monitoring biological samples at trace levels of chemicals from anthropogenic actions such as pesticides, pharmaceuticals, and hormones has become a very important subject. This work describes a method for the determination of eight compounds of different chemical classes in human urine samples. Dispersive liquid–liquid microextraction based on magnetic ionic liquids was used as the sample preparation procedure. The main parameters of the method, such as sample dilution, type, and volume of disperser solvent, amount of magnetic ionic liquids, extraction time, and pH were optimized by univariate and multivariate procedures. Validation was performed using a urine sample of a male volunteer in order to obtain a calibration curve and the main analytical parameters of merit such as limits of detection and quantification. Values varied from 3.0 to 7.5 µg/L and from 10 to 25 µg/L, respectively. Satisfactory precisions of 21% for intraday (n = 3) and 16% for interday (n = 9) were achieved. Accuracy was evaluated by relative recovery assays using different urine samples and ranged from 75 to 130%. Robustness was assured by the Lenth method. The validated procedure was applied to five urine samples from different volunteers and the hormone estrone was found in one sample.